PARENT’S KNOWLEDGE ABOUT THE IMPLEMENTATION OF PHYSICAL BULLYING TO THE FIFTH AND SIXTH GRADE TO THE STUDENTS OF THE FIRST ELEMENTARY SCHOOL OF ARJOSARI IN KALIPARE-MALANG - admin ilkes (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2017)
Bullying behaviors are deviant behaviors that has a very serious effect for the victims and it become habit that involve unbalanced social and physical power. The importance of parent’s knowledge about the implementation of bullying behaviors to the children are very important to determine a better personality to their future. The purpose of this research is to identify parent’s knowledge about the implementation of physical bullying behaviors to the fifth and sixth year’s students of Arjosari 01 Elementary School in Kalipare Sub District Malang Regency. Research design was descriptive with research variable that is parent’s knowledge about the implementation of physical bullying behaviors to the fifth and sixth year’s students. The population of this research are all parents who had the children in Arjosari 01 Elementary School there were 23 respondents and sample 23 respondents with total sampling technique. Collecting data with questionnaire and was presented in form of table. Research result showed that 56,6% or 13 respondents had fair knowledge, while 30,4% or 7 respondents had excellent knowledge, and 13% or 3 respondents had poor knowledge.It couses the respondents having a limitation in understanding all information as a source of knowledge about the implementation of physical bullying behaviors to the children, and other factors are like age, job, education, a number of children, and a source of information. Therefore to increase parent’s knowledge that is still low, nurses needs to give guidance or counseling about implementation bullying behaviors to the children.